Uaya Preventif Terhadap Vandalisme Di Kota Pasir Pengaraian (Studi Pada Satuan Polisi Pamong Praja Kabupaten Rokan Hulu) - Tutrianto, Rio; Amin, Syaidul (UIR PRESS, 2021)
Vandalism is an act of destroying and destroying a work of art or other valuables, in other words, violent and vicious destruction and destruction. The many cases of vandalism by teenagers that occur in the city of Pasir Pengaraian are one of the concerns felt by the community. The results of this study are to find out what are the Preventive Efforts and Barriers to the Vandalism phenomenon that occurred in Kota Pasir Pengaraian. The research method used in this research is qualitative research, in this case it aims to describe the actual situation related to what is happening at the research location through collecting, analyzing, and identifying in order to obtain answers to the problems that have been formulated. So this research concludes that there are several preventive efforts against vandalism in the city of Pasir Pengaraian (a study on the Civil Service Police Unit of Rokan Hulu Regency) that have been carried out such as the existence of mass outreach activities that reach all groups regarding vandalism, the main thing is the activities and coordination with various government circles, law enforcers and the general public in overcoming vandalism, then carrying out routine patrols, while there are several obstacles or obstacles for Satpol PP in carrying out their duties and functions, especially in an effort to prevent acts of vandalism, namely the absence of special regulations for handling public facilities, lack of human resources and facilities. infrastructure owned by Satpol PP, and finally there is no special room or place for public expression in channeling creativity, especially graffiti.